Informatics in the Future: Proceedings of the 11th European Computer Science Summit (ECSS 2015), Vienna, October 2015 - Werthner, Hannes; van Harmelen, Frank (Springer Nature, 2017)
Big data; Computing ethics; Women in computing; Research ethics